Improving Students' Interest and Ability in Writing Essay through Picture Media at MI Miftahul Huda Kertosono - Munir, Fathul; Fathurrahman (DEEP LEARNING: Journal of Educational Research, 2025)
One of the very important roles of teachers is to create a quality, high-quality and enjoyable learning process. The purpose of this classroom action research is to find out how much impact the increase in student interest in the use of image media is interpreted into a composition. Increasing student interest can be seen from several aspects, namely: student activity, teacher activity and the effectiveness of the learning process, and student achievement scores. The techniques used are the classroom action research approach, observation data collection techniques, and student learning outcome tests. The data obtained from both student activity and student learning outcome scores in cycles I and II in classroom action research can be interpreted as follows; (1) Student interest and ability in learning to write compositions are very good. (2) Image media really helps students in improving their imagination so that they are able to make simple sentences that become the framework of the composition and then develop them again. (3) Students are able to interpret simple sentences by linking the series of images they observe. (4) Students are able to communicate their writing based on the results of observations to their friends and to the teacher. (5) The learning process is more varied so that children become creative, active and enjoyable. (6) Learning is more effective, because it focuses on image media. (7) Learning will be conducive, because students' attention is focused on the provided image media. (8) Teachers can easily evaluate the results of children's activities, especially in terms of student interest and ability. (9) Can be used as a benchmark for subsequent learning.